2020
DOI: 10.1177/0887403419900230
|View full text |Cite
|
Sign up to set email alerts
|

Police Procedural Justice, Lawyer Procedural Justice, Judge Procedural Justice, and Satisfaction With the Criminal Justice System: Findings From a Neglected Region of the World

Abstract: Although the impact of procedural justice on citizens’ satisfaction with the police and other branches of the criminal justice system has been tested in several geopolitical contexts, this is the first study to examine the relative impacts of police procedural justice, lawyer procedural justice, and judge procedural justice on satisfaction with a country’s criminal justice system. To assess the universal applicability of procedural justice, scholars must carry out research in all geopolitical regions. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…While speculative, this may explain participants' less positive and greater variation in general perceptions of procedural justice related to police as observed in other research (see, e.g. Pryce & Wilson, 2020).…”
Section: Attitudes Towards Magistratesmentioning
confidence: 78%
“…While speculative, this may explain participants' less positive and greater variation in general perceptions of procedural justice related to police as observed in other research (see, e.g. Pryce & Wilson, 2020).…”
Section: Attitudes Towards Magistratesmentioning
confidence: 78%
“…Past research suggests that procedurally just treatment by judges is associated with more positive attitudes toward the justice system among adults (Pryce & Wilson, 2020) and that, over and above the favorability and accuracy of the court outcome, the fairness of decision making and quality of treatment by the courts was predictive of perceptions of legitimacy of the legal system (i.e., police, courts, and the law overall; Tyler & Jackson, 2014). Similarly, research has found that the procedural justice of court proceedings is directly related to individual perceptions of court legitimacy, even more so than the accuracy of decisions and the appropriateness of sentences (Tyler & Sevier, 2013).…”
Section: Juvenile Justice Systemmentioning
confidence: 99%
“…Ensuring procedural justice plays a significant role in the context of criminal-procedure law. Many studies note the positive influence of procedural justice on public trust in police and satisfaction with their work (Pryce & Wilson, 2020;Graham et al, 2020). This is also related to individuals who have committed a crime, thus, procedural justice can contribute to order improvement in correctional institutions (Maguire et al, 2021;Yasrebi-De Kom et al, 2022) and, probably, prevent the repetition of the crime.…”
Section: Introductionmentioning
confidence: 99%